The Effect of Planning, Management Commitment, and Human Resources Competency on The Absorption of The Goods and Services Budget in The Local Government of Cilacap Region, Central Java - Rasyid Mei Mustafa; Novianto Azhar; Eko Suyono; Oman Rusmana; Wahyudin Wahyudin (Jurnal Akuntansi dan Keuangan, 2022)
This study aimed to examine the influence of planning, management commitment, and human resources competency on goods and services budget absorption of Cilacap Local Government, Central Java. This study uses primary data by distributing questionnaires to the head of working units in the Cilacap regency with a number of respondents as many as 51 people during June-July 2020. Data analysis was performed by using SPSS (Statistical Package for Social Science) version 24. The results showed that the planning with a significant value of 0,035, management commitment with a significant value of 0,012, and human resource competencies with a significant value of 0,021 positively influence the absorption of good and service expenses of government Cilacap.  With these findings, this study contributes to providing empirical data on factors influencing budget absorption on Local governments in Indonesia;